On the Distribution of the Number of Calls in the Queuing System D_η|D_ξ^κ|1 - Yezhov, I. I.; Kadankov, V. F. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
For the queuing system D η|D ξ k|1, we determine the distribution of the number of calls in transient and stationary modes.